South Asia Economic Focus, Fall 2020 : Beaten or Broken? Informality and COVID-19 - World Bank (Washington, DC: World Bank, 2020)
The COVID-19 pandemic, which is still impacting South Asia, has temporarily brought the region to a near standstill. Governments proactively stabilized activity through monetary easing, fiscal stimulus, and supportive financial regulation, but the situation is fragile amid weak buffers and exhausted policy tools. South Asia’s GDP is expected to contract 7.7 percent this year, by far the largest decline on record, but uncertainty around the forecast is substantial. The informal economy in South Asia has been hit hard. Many unorganized workers, self-employed people and microenterprises have experienced a large drop in earnings as the service sectors that were affected most by the lockdowns are dominated by informality. Informal workers and firms tend to have inadequate mechanisms for coping with short-term demand and supply interruptions due to limited savings and constrained access to finance. While the poor have suffered severely during the crisis, many informal workers in the middle of the income distribution have experienced the greatest drop in earnings. Most of them are not covered by social insurance. The crisis lays bare complicated structural problems in the informal sector that need to be addressed.